La (auto) censura en el ámbito de la prensa regional (1963-1978): una propuesta para su estudio desde «los marcos sociales» de la memoria - Rubén Cabal Tejada (Cahiers de Civilisation Espagnole Contemporaine)
The purpose of this article is the historiographical analysis of a selection of testimonies referring to Asturian journalists who recall, within the framework of an oral history research, some of their experiences in relation to censorship and self-censorship processes (1963-1978). The interest of this approach is not to understand the mechanisms of censorship but the discursive contours of these processes based on the memories expressed by their protagonists. The methodology employed is original in the field of press history studies in that it applies the sociological notion of the ‘social framework of memory’. and, beyond the case study discussed here, initiates an alternative line of work in this field, in which the history of journalism is placed within the parameters of what are known as Memory Studies.